1971
DOI: 10.1002/pssb.2220450109
|View full text |Cite
|
Sign up to set email alerts
|

Singlet exciton annihilation in anthracene crystals

Abstract: The fluorescence quenching under high excitation intensities has been studied in anthracene crystals. The singlet-singlet annihilation constant of (1 f 0.5) x cm8 s-l is calculated from the quenching of fluorescence induced by a nitrogen 16ns pulse laser (A = 3371 A). The main process of quenching under longer illumination (2 x lod s) is the interaction between singlet and triplet excitons with a rate constant of (7f4) x 10-8cmS s-l.HccneaosaHo Tyrueme $nyopecUeHUm KpHcTannoB aHTpaUeHa np11 BMCOKE~X YPOBHIIX B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

1973
1973
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 7 publications
3
15
0
2
Order By: Relevance
“…We have then calculated the rate constant k s~ for the interaction by using Agranovich's theory [11] as well as Yokota and Tanimoto's formalism [ H I . The calculated rate constant kST turns out to be close to that measured by Babenko et al [3] for crystalline anthracene. We disagree with their predicted Forster radius, but have found that our larger value is actually more consistent with the data and with Agranovich's theory.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…We have then calculated the rate constant k s~ for the interaction by using Agranovich's theory [11] as well as Yokota and Tanimoto's formalism [ H I . The calculated rate constant kST turns out to be close to that measured by Babenko et al [3] for crystalline anthracene. We disagree with their predicted Forster radius, but have found that our larger value is actually more consistent with the data and with Agranovich's theory.…”
Section: Introductionsupporting
confidence: 73%
“…Process (1.1) is a form of exciton fusion, in the sense that two excitons combine to form one. The bimolecular rate constant k s~ for the process (1.1) was found [3] to be (7 4) x 10-9 cm3/s for the case of anthracene crystals and to be (1.75 f. 0.75) x 10-10 cm3/'s for anthracene in solution [4].…”
Section: Introductionmentioning
confidence: 98%
“…(19) are the wave functions of the relative motion of the excess electron and hole, the stationary states of which are characterized by the quantum indices A. Let us introduce the energy f)K, K) of the non-interacting excess electronhole pair with the help of the relationship:…”
Section: Crystal Hamiltonian In Electron Excitation Second-quantized mentioning
confidence: 99%
“…The main process of quenching of fluorescence of the anthracene crystal under long illumination was interpreted 19 as a mutual annihilation of a pair of singlet and triplet excitons leading to the formation of a triplet exciton with higher exciton energy.…”
Section: Introductionmentioning
confidence: 99%
“…According to [2] the process of recombination is associated with the dipole-dipole resonance interaction of excitons, i.e. the transition of one exciton into the higher state with double energy and the other into the ground state.…”
Section: Introductionmentioning
confidence: 99%